Southeast Kansas Climate Summary for 2024 - Matthew Sittel (Kansas Agricultural Experiment Station Research Reports, 2025)
The divisional data in this report are from the National Centers for Environmental Information (NCEI). The NCEI generated monthly divisional averages based on individual station data from observers within the 14 counties that comprise this division. The observations come from official reporting sites such as airports, as well as co-operative and citizen observers who measure both temperature and precipitation.
Keywords: southeast Kansas; precipitation; temperature; long-term climate variability